BIOCHEMICAL AND ENZYMATIC CHARACTERIZATION OF MACROPHYTE PLANT PHRAGMITES AUSTRALIS AFFECTED BY ZINC OXIDE - FADILA KHALDI; KHAOULA MENAIAIA; NOURHENE OUARTANE; NEDJOUD GRARA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The research aimed to understand the behavior of aquatic plants subjected to xenobiotics, a macrophyte plant Phragmites australis from the region of Souk-Ahras, is treated with three concentrations based on zinc oxide (ZnO) (3, 6 and 12 nmol·mL-1) for 7, 14 and 21 days. A measurement of certain biochemical and enzymatic parameters characteristic of oxidative stress allowed us to evaluate not only the effect of zinc oxide but also the behavior of Phragmites australis subjected to this nanometric molecule. The statistical analysis of the results obtained showed no significant differences in all the parameters measured, between leaves and roots. The results of the analysis of heavy metals in wastewater, revealed values lower than the Algerian norm with the exception of Zn. On the other hand, we noticed a high concentration of Zn and a low concentration of Fe and Pb. This result makes it possible to conclude that the wastewater is characterized by a pollution of the metallic type loaded with partially degradable effluents.